Influence of hydrocolloid-based edible coatings on fruit firmness and quality of nectarine (Prunus persica var. nucipersica) cv. Snow Queen at low temperature storage - JAYARAJAN, SMRUTHI; SHARMA, R R; SETHI, SHRUTI; ASREY, RAM; AWASTHI, O P; PAUL, VIJAY; BHATIA, H S; SHARMA, V P (The Indian Journal of Agricultural Sciences, 2020)
Nectarine (Prunus persica var. nucipersica) is known for its characteristic flavor and fuzzless nature in contrast to its progenitor peaches. It is an important stone fruit with immense nutrients and antioxidant capacity. The smooth texture and glossy cosmetic appeal makes the nectarine popular among the consumers as well as growers. But the postharvest life of this functional fruit is only 3-4 days under ambient conditions due to its high perishability and its unfamiliarity among the growers as its newly introduced crop causes a significant postharvest loss to the growers. Hence, this experiment was conducted to enhance the marketability of commercially important nectarine cultivar Snow Queen fruit by coating them with various plants (hydrocolloids) based edible coating. Fruits were treated with various plant based edible coating such as carboxymethyl cellulose (1%, 1.5%) and GA (gum Arabica) (8%, 10%, 12%). The fruits were dipped in various coating material and dried under ambient condition and stored at cold storage conditions (1±1 oC and 85-90% relative humidity). The observations on various physical, physiological and biochemical attributes were recorded at weekly interval. The results revealed that among the various edible coatings applied, 1% CMC and 10% GA were found to be effective in reducing the respiration rate and maintaining better fruit firmness than other concentrations of edible coating. These treatments were also better in maintaining other biochemical parameters and extended the shelf life of Snow Queen fruit to about 28 days under storage with better organoleptic properties.